OAUNI photometry of SN 2025plf and SN 2025rbs - Pereyra, Antonio (2025)
We report photometric observations of Type Ia supernovae SN 2025plf and SN 2025rbs, obtained with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging was carried out in R filter on 2025-07-25 (UT) under non-photometric conditions, with airmasses lower than 1.5. The integration times were 60x20s=1200s for SN 2025plf and 45x20s=900s for SN 2025rbs. Our measurements yielded: SN | Date (UT) | filter | seeing (") | mag, 2025plf | 2025-07-25.261 | R | 1.9 | 15.61 +/- 0.11, 2025rbs | 2025-07-25.281 | R | 2.0 | 12.19 +/- 0.01. Zero-point calibration in both cases was performed using UCAC4 field stars. The observations were gathered ~25 days after the discovery of SN 2025plf and ~11 days after that of SN 2025rbs. The OAUNI project is supported by UNI, TWAS, IGP, and ProCienciaˇConcytec (Convenio 133-2020 Fondecyt).